2021
DOI: 10.1016/j.redox.2021.101964
|View full text |Cite
|
Sign up to set email alerts
|

Redox regulation of the insulin signalling pathway

Abstract: The peptide hormone insulin is a key regulator of energy metabolism, proliferation and survival. Binding of insulin to its receptor activates the PI3K/AKT signalling pathway, which mediates fundamental cellular responses. Oxidants, in particular H 2 O 2 , have been recognised as insulin-mimetics. Treatment of cells with insulin leads to increased intracellular H 2 O 2 levels affecting the activity of downstream signalli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 176 publications
1
35
0
Order By: Relevance
“…A large number of potentially interactive pathological mechanisms may affect the insulin target tissues as well as the pancreatic islets and the intestinal tract, thus contributing to the development of metabolic dysfunction. These include chronic low-grade inflammation, redox imbalance, mitochondrial dysfunction, ER stress, alterations in plasma levels of factors involved in inter-organ communication, leakage of the intestinal barrier, and alterations in the intestinal microbiota [ 4 , 8 , [37] , [38] , [39] , [40] , [41] , [42] ].…”
Section: T2dm and Associated Metabolic Comorbiditiesmentioning
confidence: 99%
See 2 more Smart Citations
“…A large number of potentially interactive pathological mechanisms may affect the insulin target tissues as well as the pancreatic islets and the intestinal tract, thus contributing to the development of metabolic dysfunction. These include chronic low-grade inflammation, redox imbalance, mitochondrial dysfunction, ER stress, alterations in plasma levels of factors involved in inter-organ communication, leakage of the intestinal barrier, and alterations in the intestinal microbiota [ 4 , 8 , [37] , [38] , [39] , [40] , [41] , [42] ].…”
Section: T2dm and Associated Metabolic Comorbiditiesmentioning
confidence: 99%
“…In addition, the insulin-regulated fuel metabolism is closely intertwined with redox homeostasis. Reactive oxygen species (ROS), in particular H 2 O 2 , are required for proper insulin biosynthesis, secretion, and signaling [ 4 , 37 , 40 ]. ROS at low levels do not injure cells.…”
Section: T2dm and Associated Metabolic Comorbiditiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that endothelial dysfunction and vascular insulin resistance may result from the impairment of cellular adaptive mechanisms against mitochondrial dysfunction and oxidative stress such as the redox-sensitive transcription factor nuclear factor E2-related factor 2 (Nrf2) and the antioxidant response element (ARE), which modulate cellular antioxidant activity [127,128]. Insulin resistance and persistent hyperglycaemia further exacerbate redox dysregulation through a positive feedback loop [129].…”
Section: Dysregulation Of Redox Homeostasismentioning
confidence: 99%
“…SH2 (Src homology 2) domain proteins, such as the regulatory subunits of class 1A PI3K, GRB2/SOS (growth factor receptor-bound protein 2/son of sevenless), and SHP2 (SH2 domain containing protein tyrosine phosphatase-2), are activated by Tyr phosphorylation of IRS [16]. Subsequently, PIP3 (phosphatidylinositol 3,4,5-trisphosphate) is produced in the plasma membrane through the phosphorylation of PIP2 (phosphatidylinositol 4,5-bisphosphate) by PI3K and, in turn, recruits AKT, which is then activated through the phosphorylation of the T308 (threonine 308) site of protein kinase B and other analogues in aPKCs λ/ι and ζ (calcium-and diacylglycerol-independent atypical protein kinase C isoforms λ/ι and ζ) [17,18].…”
Section: Burns and Insulin Resistance: Background Of A Toxic Relationshipmentioning
confidence: 99%